Exploring the Impacts of Seagrass on Coupled Marsh-Tidal Flat Morphodynamics - Carr, Joel; Mariotti, Giulio; Fahgerazzi, Sergio; McGlathery, Karen; Wiberg, Patricia (Frontiers in Environmental Science, 2018)
1 Intertidal coastal environments are prone to changes induced by sea level rise, increases in storminess, temperature, and anthropogenic disturbances. It is unclear how changes in external drivers may affect the dynamics of low energy coastal environments because their response is non-linear, and characterized by many thresholds and discontinuities. As such, process-based modeling of the ecogeomorphic processes underlying the dynamics of these ecosystems is useful, not only to predict their change through time, but also to generate new hypotheses and research questions. Here, we used a three-point dynamic model to investigate how seagrass might affect the behavior of coupled marsh-tidal flat systems. The model directly incorporates ecogeomorphological feedbacks among wind waves, salt marsh vegetation, allochthonous sediment loading, seagrasses and sea level rise. The model was applied to examine potential behaviors of salt marsh systems in the Virginia coastal bays. Differences due to the presence or absence of seagrass and stochastic versus constant drivers lead to the emergence of complex behaviors in the coupled salt marsh-tidal flat system. In intertidal areas without seagrass, small tidal flats are unlikely to expand and provide enough sediment to the salt marshes to combat sea level rise. However, as the tidal flat expands, the concurrent increase in sediment supply due to wave-induced processes allows for the salt marsh to maintain pace with sea level at the expense of salt marsh extent. The presence of seagrass has two effects: 1) it decreases near bed shear stresses thus reducing the sediment flux to the salt marsh platform; 2) it reduces the wave energy acting on the salt marsh scarp, thus reducing boundary erosion. Model results indicate that the reductions in wave power and near bed shear stresses when seagrass is present provide an overall stabilizing effect on the coupled marsh-tidal flat system; but as water depth increases due to sea level rise or as external sediment supply increases, light conditions decline and the system reverts to that of a bare tidal flat.